Comparing and deciding: a historical note on education policy - Justino Magalhães (Springer, 2013)
This article provides a 'lineage' of decisions related to education policy which takes comparison as its motive, knowledge and method. A conceptual chain of world system, internationalization, convergence in education and globalization is briefly outlined. The paper examines decision-making in education policy according to agreement, mainstreaming and production criteria, taking Latin America as the linkage and the European Community as the construction. Reasoning and enlightenment are gathered in different fields of history: culture, economics, politics and education. The present paper applies a core structuring epistemology -culled from a variety of academic domains- with comparison and decision underpinning a complex rationale where time, space, materiality, knowledge, ideas, action, and evaluation all intersect.